IMPLEMENTASI RESEP STANDAR DALAM MENJAGA KONSISTENSI KUALITAS MAKANAN (STUDI DI RESTORAN SEADUCTION FRII HOTEL BALI ECHO BEACH CANGGU BALI) - I Made Ngurah Ryan Yasa Permana; Ni Putu Yunik Anggreni; Ni Wayan Mekarini (Universitas Triatma Mulya, 2023)
The basic function of standard recipes as a control over food preparation. Processing food using standard recipes will produce dishes that are consistent in terms of taste and quality. FRii Hotel Bali Echo Beach is a three-star hotel that applies standard recipes on handling food processing. This research was conducted to find out how standard recipes is implemented at the Seaduction FRii Hotel Bali Echo Beach Restaurant as well as the obstacles in the implementation process, and efforts to overcome them. This research uses standard prescription theory. The data analysis technique used is descriptive qualitative which describes, illustrates and explains in detail the problems studied. Data collection methods used include observation, interviews and documentation study. The research results show that (a) the implementation of standard recipes at the Seaduction Restaurant is carried out using a training method consisting of making standard recipes, briefings and practice, as well as controlling the supply and preparation of raw materials, preparation of cooking utensils, manufacturing process and serving; (b) The restaurant faced obstacles in the process of implementing standard recipes so efforts are made to overcome these obstacles by monitoring discipline, warnings, and even certain funishment.